The Role of Larval Source Management (LSM) as Malaria Elimination - Rochmadina Suci Bestari; Amelia Sri Mulyani (HM Publisher, 2022)
Malaria is one of the infectious diseases that are still a problem in Indonesia and the world. The Indonesian government in collaboration with WHO had have guidelines to prevent malaria transmission through the distribution of mosquito nets (long-lasting insecticidal net), Indoor Residual Spray, use of repellents, and others. However, advances in malaria elimination measures had also been accompanied by rapidly growing resistance and changes in vector genetics. This study aimed to know the effectiveness of LSM for malaria elimination. This study used a literature review method using online-based databases including Google Scholar, Pubmed, Science Direct, and Springer, limited to the last 15 years, boolean operator “Malaria” OR “Malaria Control” OR “Malaria Elimination” AND “LarvalSource Management”. There were 1,716 articles found and then excluded according to the restriction criteria, 8 articles were reviewed. Based on the 8 articles that had been obtained and analyzed, it was found that 1 article showed fully practised LSM and 7 articles had practised larviciding as representatives of the LSM program. Larval source management (LSM) can effectively reduce the number of Anopheles sp. mosquito larvae, whether used according to complete action or only one action. All articles stated that LSM was an effective program and can be used for malaria elimination in the future. Larval source management (LSM) was an effective program for malaria elimination.